Identifying Barriers to Idiopathic Pulmonary Fibrosis Treatment: A Survey of Patient and Physician Views - Maher, Toby M.; Swigris, Jeffrey J.; Kreuter, Michael; Wijsenbeek, Marlies; Cassidy, Nicola; Ireland, Lucy; Axmann, Judit; Nathan, Steven D. (Respiration, 2018)
Background: Antifibrotics are recommended for the treatment of individuals with idiopathic pulmonary fibrosis (IPF), but treatment use remains at ∼60%. Objective: To investigate the views of individuals with IPF and pulmonologists on the diagnosis and management of IPF to understand treatment patterns. Methods: Interviews and/or online surveys were completed by patients and pulmonologists from Canada, France, Germany, Italy, Spain, and the UK. Responses from physicians were analyzed by time between diagnosis and treatment initiation in the majority of patients with IPF (group A, > 4 months; group B, ≤4 months). Statistical comparisons between physicians were undertaken using z tests, with p < 0.05 considered statistically significant. Results: The physicians in group A saw fewer patients, were less comfortable discussing the IPF prognosis with patients, and had less belief in the benefits of antifibrotic treatments than the physicians in group B. These physicians’ attitudes contrasted with those of the patients, who wanted more information about the IPF prognosis and pharmacological treatment options at diagnosis and were more concerned about preventing disease progression than avoiding medication side effects. Differences between countries were found regarding physicians’ comfort in discussing the prognosis at diagnosis and access to care. Conclusions: Several barriers to antifibrotic treatment, principally reflecting the differing views and values of patients and physicians, were identified in this study, suggesting a need for better patient-physician communication about pharmacological therapy for IPF.
Gesehen am 12.09.2019